Financial Literacy Training In The South Alai Village Community, lembak District, South Sumatra - Vhika Meiriasari; Mutiara Kemala Ratu; Emilda; Kgs. M. Nurkholis (LPPM Universitas Muhammadiyah Tasikmalaya, 2024)
Alai Selatan Village is one of 10 villages in Lembak sub-district, has an area 0f 1.219 hectares. The activity was carried out at the KKNT location, Alai Selatan Village, Lembak District, South Sumatra. The aim of carrying out this community service activity is to provide education about financial literacy to the public so that it can reduce the risks posed by illegal financial products and the public can choose investments that are good and safe for them. The method used in this community service activity is using the training method with a total 0f 25 participants. From the results of the pre-test and post-test given during the training, it can be seen that there has been an increase in knowledge about financial literacy. During the pre-test, only 2 participants had a good level of understanding, 8 participants had a sufficient level of understanding and 15 people had a poor level of understanding. During the post-test there was an increase in the number of 8 participants with a good level of understanding, 14 participants with a sufficient level of understanding and 3 participants with a poor level of understanding.